Family Meetings in the Intensive Care Unit During the Coronavirus Disease 2019 Pandemic. (March 2021) - Piscitello, Gina M.; Fukushima, Corinna M.; Saulitis, Anna K.; Tian, Katherine T.; Hwang, Jennifer; Gupta, Shreya; Sheldon, Mark
Purpose: Visitor restrictions during the COVID-19 pandemic limit in-person family meetings for hospitalized patients. We aimed to evaluate the quantity of family meetings by telephone, video and in-person during the COVID-19 pandemic by manual chart review. Secondary outcomes included rate of change in patient goals of care between video and in-person meetings, the timing of family meetings, and variability in meetings by race and ethnicity. Methods: A retrospective cohort study evaluated patients admitted to the intensive care unit at an urban academic hospital between March and June 2020. Patients lacking decision-making capacity and receiving a referral for a video meeting were included in this study. Results: Most patients meeting inclusion criteria (N = 61/481, 13%) had COVID-19 pneumonia (n = 57/61, 93%). A total of 650 documented family meetings occurred. Few occurred in-person (n = 70/650, 11%) or discussed goals of care (n = 233/650, 36%). For meetings discussing goals of care, changes in patient goals of care occurred more often for in-person meetings rather than by video (36% vs. 11%, p = 0.0006). The average time to the first goals of care family meeting was 11.4 days from admission. More documented telephone meetings per admission were observed for White (10.5, SD 9.5) and Black/African-American (7.1, SD 6.6) patients compared to Hispanic or Latino patients (4.9, SD 4.9) (p = 0.02). Conclusions: During this period of strict visitor restrictions, few family meetings occurred in-person. Statistically significant fewer changes in patient goals of care occurred following video meetings compared to in-person meetings, providing support limiting in-person meetings may affect patient care.